Minimal mass and self-stress analysis for innovative V-Expander tensegrity cells. (1st February 2019) - Fraddosio, Aguinaldo; Pavone, Gaetano; Piccioni, Mario Daniele
Abstract: Tensegrity structures are an intriguing kind of structures by virtue of their deployability, scalability and high stiffness to mass ratio. Fraddosio et al. recently proposed a family of five innovative V-Expander elementary tensegrity cells, characterized by an increasing degree of geometrical complexity, and designed as a morphological evolution of a concept originally proposed by Motro and Raducanu. Here, we study the mechanical behavior of these innovative V-Expander elementary tensegrity cells by referring to different topologies; in particular, we analyze for such cells the feasible self-stress states in the cases in which the components in compression are composed of 2, 3, 4 and 6 struts, respectively. In addition, we evaluate the minimal mass of the cells taking into account the buckling strength of members in the self-equilibrium states according to the indications of standard building codes.